Sistem Pendukung Keputusan Pemilihan Working Cafe Terbaik di Sekitar UPNVJ Pondok Labu Menggunakan Metode SAW - Jihan Aulia Rahmawati; Sekar Purbaningrum; Avriel Valent Angela; Zatin Niqotaini (Universitas Aisyiyah Surakarta, 2026)
Choosing the ideal café for studying is crucial for improving student productivity. Students often face difficulties in selecting the café that best suits their needs due to the wide range of café options around UPN “Veteran” Jakarta Pondok Labu, each offering different facilities. This study aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to help students objectively choose the most suitable café. The criteria considered in this study include Wi-Fi quality, crowd level, number of power outlets, price, and distance from campus. Data were collected through direct observation and questionnaires distributed to students at UPN “Veteran” Jakarta. Five cafés were evaluated as alternatives: Beskabean UPN “Veteran” Jakarta, Sehela Kopi, Unara Coffee, Cuplink Coffee, and Fern Coffee House. The SAW method was applied through determining criterion weights, constructing a decision matrix, normalizing data, calculating preference values, and ranking the alternatives. The results indicate that Sehela Kopi achieved the highest preference value of 0.961 and was identified as the best café recommendation. These findings demonstrate that the SAW method can provide objective and useful recommendations for selecting cafés that meet students’ needs.